Evaluation of The Cyber Religious Education Media with PIECES Framework - Danuri, Muhamad; Suistiyo, Heru; Wahyono (Journal of Information Systems and Digital Technologies, 2020)
Community users of digital technologies in the Internet and various facilities such as social media, internet, games and various other applications provide a variety of positive and negative effects. efficiency, safety, comfort and effectiveness are positives of this technology but there are also negative impacts such as the decline of social behavior, crime and moral vulnerability. Although there have been internet ethical guidelines such as Cyber Ethics but have not been able to play a maximum role to be able to control the negative impact. Cyber religious is a model of internet user control of amoral and criminal acts, which can be applied to various elements related to the internet world. One of the applications of cyber religious for user control internet with applications that can detect immoral behavior or crime on the internet through detection on the browser used. It’s so easy for someone to access internet information resulting in Uncontrolled Internet users. This can lead to problems such as dangerous access to cysts, pornography, crime, cruelty, abnormal behavior and committing criminal acts to others. Cyber religius proccesing is check the internet access of a person, if found any indication of immorality or crime then the system will provide warning and or provide other information more useful. This research provides various models of cyber religus achitecture with adoptation from some research about connection control with internet network. Each model influences different communities access from small office (LAN), large office (MAN), Access from any country and access to the world.